Managing talent : a critical appreciation - Swailes, Stephen (Emerald Publishing Limited, 2020)
Managing Talent: A Critical Appreciation is aimed at management researchers seeking alternative and sometimes suppressed insights into talent theory and practice. The book gives alternative critical understandings of management innovations and highlight fresh insights into popular management ideas, practices and the literatures that surrounds them.
Prelims -- Introduction -- Chapter 1: Arbitrariness, Individuality, and the Absence of Work Identity in Talent Management -- Chapter 2: Social and Natural Constituents of Talent: A Critical Appreciation -- Chapter 3: Some Critical Reflections on the Relevance of Talent Management Research -- Chapter 4: The Rhetoric, Politics and Reality of Talent Management: Insider Perspectives -- Chapter 5: Leadership Derailment: A Neglected Field in Talent Management -- Chapter 6: The Missing Link: The Role of Line Managers and Leadership in Implementing Talent Management -- Chapter 7: How Inclusive Can Exclusive Talent Management Be? -- Chapter 8: Critical Feminist Organisation Studies and Talent Management: Re-imagining Transnational, Intersectional and Postcolonial Agendas -- Chapter 9: The Paradox of Attracting Key Talent in the Canadian Cannabis Industry: Turning Over a New Leaf -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Ability -- Management; Personnel management; Business & Economics -- Strategic Planning; Personnel & human resources management